HYDROGEL-BASED WOUND DRESSING IN THE TREATMENT OF DIABETIC FOOT ULCERS: A NARRATIVE REVIEW - Sembiring, Faisal Rozi; Sazli, Brama Ihsan (TALENTA Publisher, Universitas Sumatera Utara, 2024)
ABSTRACTBackground: The aim of this case study is to determine the effectiveness of hydrogel-based wound dressing (HBWD) in the treatment of diabetic foot ulcer (DFU) in diabetic patients.Methods: Method in this case study is evidence-based case report. The clinical question used: Are HBWDs effective in the treatment of DFU, especially in the limited-resources healthcare facilities? To answer this question, we search the evidence from PubMed, Cochrane Database, Semantic Scholar, and Google Scholar with various keywords based on the clinical question. The studies were selected based on pre-determined inclusion and exclusion criterias and were critically appraised.Results: Four randomized controlled trials (RCTs) that met the inclusion and exclusion criterias were found. There are no significant difference in reduction of ulcer area (RUA) rate or complete wound closure (CWC) rate in all RCTs. When compared to control or non-hydrogel group, three studies reported some favoring aspect in HBWD group, such as less inflammatory signs and faster CWC mean time. Conclusion: HBWDs are recommended in the treatment of DFU because they are widely available, cost-effective, and relatively easy to use.